Exploring the Impact of Product Quality and Social Media Promotion on Purchase Decisions through Customer Satisfaction - Ni Luh Nurkariani; Dewa Ayu Seri Naraswari; Mazzlida Mat Deli (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Understanding factors that influence consumer purchasing decisions is essential for improving customer satisfaction and business performance. This study investigates the effect of product quality and social media promotion on consumers’ purchasing decisions for Banana Stem Chopping Machines at Denita Welding and Lathe Workshop, with customer satisfaction as a mediating variable. A quantitative approach was used, collecting data via online questionnaires and direct field surveys from 64 respondents who had purchased the machines in the past five years. Data were analyzed using Partial Least Squares (PLS) within Structural Equation Modeling (SEM) via SmartPLS. The results show that product quality, social media promotion, and customer satisfaction significantly affect purchase decisions. In addition, product quality and social media promotion enhance customer satisfaction, which in turn drives purchasing behavior. The study highlights the importance of maintaining high product quality and implementing effective social media strategies to increase customer satisfaction and purchase decisions.